Managers As Mentors : Building Partnerships for Learning - Bell, Chip R. (Berrett-Koehler Publishers, 2013)
Leaders Creating Leaders This latest edition of the classic Managers as Mentors is a rapid-fire read that guides leaders in helping associates grow in today?s tumultuous organizations. Thoroughly revised throughout with twelve new chapters, this edition places increased emphasis on the mentor acting as a learning catalyst with the protg rather than simply handing down knowledge. As with previous editions, a fictional case study of a mentor-protg relationship runs through the book. But now this is augmented with interviews with six top US CEOs. New chapters cover topics such as the role of mentoring in spurring innovation and mentoring a diverse and dispersed workforce accustomed to interacting digitally. Also new to this edition is the Mentor?s Toolkit, six resources to help in developing the mentor-protg relationship. This hands-on guide teaches leaders to be the kind of confident coaches integral to learning organizations.?Continual learning is a key to effective leadership?Managers as Mentors is a practical yet powerful book for helping leaders make continual learning a valuable addition to their strategy.??Mike Krzyzewski, Head Coach, Duke University Men?s Basketball, 2010 NCAA Champions?Mentoring is the highest of the teaching arts, and in this new edition, Chip Bell and Marshall Goldsmith have skillfully crafted the essential handbook for all those who are trusted advisors to aspiring leaders.??Jim Kouzes, coauthor of The Leadership Challenge and Dean?s Executive Fellow of Leadership, Leavey School of Business, Santa Clara University?Managers as Mentors will be the indispensable handbook of managers/leaders across the sectors.??Frances Hesselbein, President and CEO, The Frances Hesselbein Leadership Institute, and former CEO, Girls Scouts of the USA.